Macronutrients uptake rate and biomass partitioning during early growth of Jatropha plants - Santos, Elcio; Macedo, Fernando; Zanchim, Bruno; Camacho, Marcos; Lavres, José (Revista Ciência Agronômica, 2017)
Jatropha seeds oil can replace fossil fuels, but the nutrient supply management for this species is not fully described. The objective with this work was to establish curves of macronutrient (nitrogen - N; phosphorus - P; potassium - K; calcium - Ca; magnesium - Mg and sulfur - S) content in leaves, stem and roots, and to evaluate the relative growth rate (RGR), absolute growth rate (AGR) and the foliar mass ratio (FMR). The experiment was arranged in completely randomized design with five replications. Jatropha plants were grown in nutrient solution and collected at intervals of 14 up to 119 days after treatments started. The period of highest uptake of nutrients occurred from 7 to 35 days after treatments started, which coincides with highest AGR, RGR, FMR and accumulation of dry biomass. The highest Ca and Mg accumulation occurred in the leaves (respectively 48% and 47% of the total taken up), while N, K, S and P were mostly accumulated in the stem (58%, 56%, 56% and 53%, respectively). The nutrients more taken up by Jatropha plants were N and Ca, and the order of macronutrients uptake was:  N > Ca > K > Mg > S > P.  Jatropha plants have shown high macronutrients content on its early development, indicating the importance of nutritional management to achieve reliable biomass yield.